On‐surface Synthesis of a Semiconducting 2D Metal–Organic Framework Cu3(C6O6) Exhibiting Dispersive Electronic Bands. (16th January 2020) - Zhang, Ran; Liu, Jing; Gao, Yifan; Hua, Muqing; Xia, Bowen; Knecht, Peter; Papageorgiou, Anthoula C.; Reichert, Joachim; Barth, Johannes V.; Xu, Hu; Huang, Li; Lin, Nian
Abstract: A 2D metal–organic framework (2D‐MOF) was formed on a Cu(111) substrate using benzenehexol molecules. By means of a combination of scanning tunneling microscopy and spectroscopy, X‐ray photoelectron spectroscopy and density‐functional theory, the structure of the 2D‐MOF is determined to be Cu3 (C6 O6 ), which is stabilized by O–Cu–O bonding motifs. We find that upon adsorption on Cu(111), the 2D‐MOF features a semiconductor band structure with a direct band gap of 1.5 eV. The O–Cu–O bonds offer efficient charge delocalization, which gives rise to a highly dispersive conduction band with an effective mass of 0.45 me at the band bottom, implying a high electron mobility in this material. Abstract : Mut zur Lücke : Ein zweidimensionales Metall‐organisches Einzelschichtgerüst hat eine direkte Bandlücke von 1.5 eV sowie ein hoch dispersives Leitungsband. Seine effektive Masse beträgt 0.45 me, und es liefert eine ausgezeichnete Ladungsmobilität.